Child and Adolescent Sexual Abuse in Women Seeking Help for Sexual and Reproductive Mental Health Problems: Prevalence, Characteristics, and Disclosure. Issue 3 (3rd April 2017) - López, Sílvia; Faro, Concepció; Lopetegui, Lourdes; Pujol-Ribera, Enriqueta; Monteagudo, Mònica; Avecilla-Palau, Àngels; Martínez, Cristina; Cobo, Jesús; Fernández, María-Isabel
ABSTRACT: This is a multicentric, descriptive, cross-sectional study of child and adolescent sexual abuse in women over 18 years in 24 primary care sexual and reproductive health centers in Catalonia. A total of 1, 013 women were recruited; 345 (37.6%, 95% CI: 34.6–40.9) reported exposure to child sexual abuse: 32.4% disclosed being touched in a sexual way, and 9.6% reported completed sexual intercourse. Abuse occured before the age of 13 in 63.4% of respondents. The perpetrator was a relative or an acquaintance in almost 80% of cases. The risk was higher among women of Central or South American origin (OR: 2.86; 95% CI: 1.33–6.12). Only 31.9% of women disclosed the abuse and 17.3% were blamed. Abuse that involved attempted or completed sexual intercourse was significantly associated with recurrence, physical violence, and revictimization in adulthood.